2021
DOI: 10.1089/neur.2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Class on Regional Brain Volume, Cognition, and Other Neuropsychiatric Outcomes among Professional Fighters

Abstract: Traumatic brain injury (TBI) is a common source of functional impairment among athletes, military personnel, and the general population. Professional fighters in both boxing and mixed martial arts (MMA) are at particular risk for repetitive TBI and may provide valuable insight into both the pathophysiology of TBI and its consequences. Currently, effects of fighter weight class on brain volumetrics (regional and total) and functional outcomes are unknown. Fifty-three boxers and 103 MMA fighters participating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…We found that years of boxing had a significant association with the reduction of right-sided thalamic volume in boxers. This is in line with previous prospective studies that reported greater decline in thalamic volume with increased fight exposure [ 15 , 51 ]; however, unlike in the aforementioned study by Bray et al. we were not able to test the interaction between weight class and fight exposure regarding different brain volumes due to our small study group.…”
Section: Discussionsupporting
confidence: 90%
“…We found that years of boxing had a significant association with the reduction of right-sided thalamic volume in boxers. This is in line with previous prospective studies that reported greater decline in thalamic volume with increased fight exposure [ 15 , 51 ]; however, unlike in the aforementioned study by Bray et al. we were not able to test the interaction between weight class and fight exposure regarding different brain volumes due to our small study group.…”
Section: Discussionsupporting
confidence: 90%
“…When fighters of similar weight and physical conditioning train or compete against each other, it minimizes potential advantages or disadvantages arising from substantial differences in size, strength, and reach (Spanias et al, 2019). Ensuring similar aerobic and anaerobic conditions among athletes allows them to showcase their skills and techniques without encountering excessive physical mismatches (Bray et al, 2021;Chernozub et al, 2022). Furthermore, comparing weight divisions with closely matched weights enhances the safety of the athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of injuries such as abrasion, contusion, fractures, strains, and sprains were also observed between MMA athletes [4,31,35,36]. Head traumas are a major concern due to the negative effects that this injury leads to, such as headaches, loss of balance, visual impairments, emotional disturbance, and neurocognitive deficits [38,39,[46][47][48]. At professional events, such as the UFC, a head injury rate of 35 injuries per 100AE is reported [43].…”
Section: Weight Lossmentioning
confidence: 99%
“…Regarding brain injuries, a longitudinal study demonstrated temporal trends in structure and cognition-positive and neuropsychiatric outcomes that diverged when investigated by weight category and type of combat sport [48]. This evidence suggests that, although weight category has not been preliminarily identified as a determinant of early brain health among professional athletes, it modifies the course of neurodegenerative transformations over time, as the similar neurological effects of repetitive impacts on the head (RHIs) are concentrated [48]. Currently, few studies have investigated the effects of head accelerations and its outcomes.…”
Section: Weight Lossmentioning
confidence: 99%